Multiple resistance to carcinogens and xenobiotics: P-glycoproteins as universal detoxifiers - Efferth, Thomas; Volm, Manfred (Archives of toxicology, 2017)
The detoxification of toxic substances is of general relevance in all biological systems. The plethora of exogenous xenobiotic compounds and endogenous toxic metabolic products explains the evolutionary pressure of all organisms to develop molecular mechanisms to detoxify and excrete harmful substances from the body. P-glycoprotein and other members of the ATP-binding cassette (ABC) transporter family extrude innumerous chemical compounds out of cells. Their specific expression in diverse biological contexts cause different phenotypes: (1) multidrug resistance (MDR) and thus failure of cancer chemotherapy, (2) avoidance of accumulation of carcinogens and prevention of carcinogenesis in healthy tissues, (3) absorption, distribution, metabolization and excretion (ADME) of pharmacological drugs in human patients, (4) protection from environmental toxins in aquatic organisms (multi-xenobiotic resistance, MXR). Hence ABC-transporters may have opposing effects for organismic health reaching from harmful in MDR of tumors to beneficial for maintenance of health in MXR. While their inhibition by specific inhibitors may improve treatment success in oncology and avoid carcinogenesis, blocking of ABC-transporter-driven efflux by environmental pollutants leads to ecotoxicological consequences in marine biotopes. Poisoned seafood may enter the food-chain and cause intoxications in human beings. As exemplified with ABC-transporters, joining forces in interdisciplinary research may, therefore, be a wise strategy to fight problems in human medicine and environmental sciences.